Prevalence Of Osteopenia And Osteoporosis: The Assessment Of Osteoporosis Knowledge, Health Belief And Self-Efficacy Among Patients With Type 2 Diabetes Mellitus In Penang - Ameer, Shaymaa Abd Alwahed Abdul (2014)
Type 2 diabetes mellitus (T2DM) and osteoporosis are both chronic conditions and the relationship between them is complex. Knowledge, health belief and self-efficacy toward osteoporosis are fundamental to all osteoporosis management programs and are often a pre-requisite for initiating desired behavioural changes. Therefore, the aims of the present study were to assess the prevalence of osteoporotic conditions and the level of knowledge, health belief and self-efficacy toward osteoporosis among T2DM patients in Penang.